Curing characteristics, swelling, and mechanical properties of natural rubber/nitrile butadiene rubber blends with and without compatibilizer - Arum Yuniari; Hesty Eka Mayasari; Ike Setyorini (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2017)
The use of methyl methacrylate butadiene styrene (MBS) as a compatibilizer for natural rubber (NR) and nitrile butadiene rubber (NBR) blends has been investigated. Research on the cure characteristics, mechanical properties, swelling, and morphology (SEM) has been conducted to determine the compatibility of NR/NBR blends in the presence of MBS. Based on the cure characteristics, it is indicated that the presence of MBS was affected significantly by maximum and minimum torque. The addition of MBS improved the mechanical properties and the oil resistance of NR/NBR blends due to the compatibility and better interfacial adhesion between rubber phases. The experiment showed that MBS loading by 2.5 phr was the optimum level for NR/NBR blends.